Latitudinal comparison of the thermal biology in the endemic lizard Liolaemus multimaculatus. (February 2020) - Stellatelli, Oscar Aníbal; Vega, Laura E.; Block, Carolina; Rocca, Camila; Bellagamba, Patricio Juan; Cruz, Félix Benjamín
Abstract: Thermoregulation in ectotherms may be modulated by climatic variability across geographic gradients. Environmental temperature varies along latitudinal clines resulting in heterogeneous thermal resource availability, which generally induces ectotherms to use compensatory mechanisms to thermoregulate. Lizards can accommodate to ambient temperature changes through a combination of adaptive evolution and behavioral and physiological plasticity. We studied the thermal ecology of the endangered endemic lizard Liolaemus multimaculatus at six different sites distributed from the northern to southern areas of the distribution (700 km) in the Atlantic dune barriers of Argentina, and even including the borders areas of the distribution range. Environmental temperatures and relative humidity showed a strong contrast between northern and southern limits of the distribution range. The northern localities had operative temperatures ( T e) above the range of preferred temperatures ( T set), instead, the southern localities had large proportion of T es within the T set. Although these different climatic conditions may constrain the thermal biology of L. multimaculatus, individuals from all localities maintained relatively similar field body temperatures (X T b = 34.07 ± 3.02 °C), suggesting that this parameter is conservative. Thermal preference partially reflected latitudinal temperature gradient, since lizards from the two southernmost localities showed the lowest T sel and T set. Thermoregulatory efficiency differed among localities, since E values in the northern localities ( E = 0.53–0.69) showed less variability than those of southern localities ( E = 0.14–0.67). Although L. multimaculatus employed a strategy of having a conservative T b and being able to acclimatize the thermal preference to copes with latitudinal changes in the thermal environment, other local factors, such as ecological interactions, may also impose limitations to thermoregulation and this may interfered in the interpretation of results at wider spatial scale. Highlights: We studied the thermal biology of Liolaemus multimaculatus in a latitudinal gradient. Field body temperature were constant despite of latitude. Individuals of different sites used similar thermal patches. Preferred temperatures decreased up to 3 °C with latitude. Changes in thermal preferences and behavioral plasticity improve thermoregulation.